DEVELOPMENT OF LIGHT AND QR-CODE ASSISTED BRAIN LOBES AND THEIR TASKS MODEL AND VIEWS OF TEACHER CANDIDATES ON THE MODEL: - - Akbay, Seher; Ozel, Cigdem Alev; Özlem Taşdelen; Önder, Ayşe Nesibe; Güven Yıldırım, Ezgi (International Online Journal of Education and Teaching, 2022)
The purpose of this study is to determine teacher candidates’ opinions on the Light and QR-Code Assisted Brain Lobes and their Tasks model, which is a unique design that differentiates itself from other studies in the literature. The study employed the basic qualitative research approach. Teacher candidates studying at the Faculty of Education of a state university in Ankara in the fall semester 2021-2022 were included in the study. The study group consisted of 50 teacher candidates studying in the Biology Education and Science Education. The Material Assessment form was the data collection tool for the study. The first part of the form, contains a material evaluation rubric. The second part of the form had semi-structured interview questions aimed at getting more detailed views from participants about the model. From the material evaluation rubric, a material evaluation score was obtained. A five-stage thematic analysis method was used in the analysis of qualitative data obtained through open-ended questions. As a result, the model can be considered a teaching material that can be used effectively in the teaching of the relevant subject. It was determined that teacher candidates expressed many positive opinions about the model designed to teach the brain lobes.